How does tree regeneration respond to mixed‐severity fire in the western Oregon Cascades, USA? - Christopher J. Dunn; James D. Johnston; Matthew J. Reilly; John D. Bailey; Rebecca A. Miller (Ecosphere, 2020)
Abstract Dendroecological studies of historical tree recruitment patterns suggest mixed‐severity fire effects are common in Douglas‐fir/western hemlock forests of the Pacific Northwest (PNW), USA, but empirical studies linking observed fire severity to tree regeneration response are needed to expand our understanding into the functional role of fire in this forest type. Recent increases in mixed‐severity fires offered this opportunity, so we quantified the abundance, spatial distribution, species richness, and community composition of regenerating trees across a mixed‐severity fire gradient (unburned–high‐severity fire) 10 and 22 yr post‐fire, and use our results to inform a discussion of fire's functional role in western Oregon Cascades Douglas‐fir forests. Regeneration abundance was unimodal across the fire severity gradient such that the greatest mean abundance followed moderate‐severity fire (25–75% basal area mortality). Similarly, the greatest number of species was present within the most 25‐m2 regeneration quadrants (most extensive distribution) following moderate‐severity fire, relative to any other fire severity class. On average, species richness also exhibited a unimodal distribution across the severity gradient, increasing by 100% in stands that experienced moderate‐severity fire relative to unburned forests or following high‐severity fire, as predicted by the Intermediate Disturbance Hypothesis. Several distinct regeneration communities emerged across the fire severity gradient, including early seral tree communities indicative of those observed in initial and relay floristics successional models for this forest type. Most significantly, moderate‐severity fire alters successional trajectories and facilitates the establishment of a more diverse tree regeneration community than observed following low‐ or high‐severity fire. These communities are reflective of the diverse overstory communities commonly encountered throughout this forest type. The emergence of these diverse forests is unlikely to develop or persist in the absence of moderate‐severity fire effects, and may be perpetuated longer by recurring moderate‐severity fire relative to experiencing stand replacing fire. Therefore, moderate‐severity fire may be the most functionally important fire effect in Douglas‐fir forests and should be better represented in successional models and more prominent in ecologically based fire and forest management.